Orientation Relationship of FeNiC and FeNiCSi from Variant Detection in EBSD Data - Mattis Seehaus; Risheng Pei; Sandra Korte-Kerzel; Stefanie Sandlöbes-Haut (Crystals, 2023)
The determination of orientation relationships in dual or multi-phase materials is very important in the field of interface engineering for the design of materials with tailored properties. In this work, a code is developed for the automated and statistical analysis of the orientation relationship of electron backscatter diffraction data. The code is applied to the example of Fe-Ni-(Si)-C alloys containing lenticular martensite and retained austenite, and it is shown that the orientation relationship (OR) corresponds to the Greninger–Troiano OR and that a statistically reliable investigation of the OR between the retained austenite and the related martensite variants is feasible using the code developed in this study.